(untitled) (Innovative professional education, 2023)
The publication deals with the method of producing electronic training manuals using the Google Sites cloud technology, which is now a service with a multi-vector menu, which allows not only to arrange the electronic training text, but also to design the educational material in tables, diagrams, blocks, add videos, images, presentations, create a system for diagnosing program learning outcomes (tests, creative tasks, exercises of various types). The essence of the concept "methodology of creating electronic manuals" is formulated, the approaches, classic and specific principles, stages of compiling electronic manuals using the Google Sites cloud service are defined.